Assessment of Workers’ Body Temperature and Workload in Tomato Production Greenhouse Work - Rizky Silalahi; Mirwan Ushada; Mohammad Affan Fajar Fallah; Kotaro Takayama; Noriko Takahashi; Hiroshige Nishina (APTA and DTIP FTP UGM, 2017)
Many workers work in the tomato production greenhouse in Japan, exposed to unfavorable environmental conditions during their work, especially in the summer season. In this study, workers’ body temperatures of internal, facial, and head area temperature were measured, so did the workers’ workload. They were related to environmental conditions of solar radiation and air temperature to clarify their relationships. Three workers in semi-commercial tomato production greenhouse were employed for this research. Jobs were classified into upper and lower canopy job, to examine the working condition in the greenhouse. Ear thermometer and thermal camera were used to measure worker’s body temperatures. Workload of the jobs was assessed and determined the level with Heart Rate Reserve (HRR). Workers’ heart rate itselves was measured using finger pulseoxymeter. Significant correlations were found between workers’ body temperature and environmental conditions. Worker’s workload could change on changing environmental conditions. Workload level of tomato production greenhouse job is considered low, as the job relatively does not require heavy physical work.